Creep properties of siltstone-like materials with different unloading confining pressures under seepage - Zhang, Xiangdong; Zhou, Zhongchao; Yang, Jianjun; Pang, Shuai; Geng, Jie; Li, Wenliang; Zhang, Xuefeng (Frontiers in Earth Science, 2022)
Deep enclosing rock has non-homogenous dense joint and fissure development characteristics. Under the influence of multiple factors, such as high ground stress and high osmotic pressure, soft rocks are prone to damage and large deformations, leading to deformation and instability in the enclosing rocks and the failure and destruction of the supporting structure, eventually leading to accidents. This study investigated the damage law of deep soft rocks and the creep properties of siltstone-like materials with different unloading confining pressures under the coupling effect of high stress and seepage fields. Subsequently, the laws relating transient strain, creep deformation, and creep rate under each condition were analyzed. This study suggested that the radial and axial creep curves have similar variation patterns. However, the radial creep value is greater than the axial creep value under unloading confining pressure. Creep test results from siltstone-like specimens under seepage confirmed that the constitutive relation of siltstone-like specimens with different unloading confining pressures under seepage was obtained with an improved visco-elasto-plastic model whilst considering the coupling effect of fissure and seepage flow. The correlation coefficients of the calculated model values with the experimental values all exceeded 0.9178, as obtained by the non-linear least-squares fitting, accurately characterizing the creep process of fissured siltstone.